Tongue mobility in patients with cerebral palsy - Živković Zorica; Golubović Slavica (Vojnosanitetski Pregled)
Background/Aim. In children with cerebral palsy speech is a big problem. Speech of these children is more or less understandable, depending on the degree of reduced mobility of articulatory organs. Reduced mobility is affected by inability to control facial grimacing and poor muscle strength when performing targeted movements. The aim of this study was to determine the mobility of tongue in patients with cerebral palsy. Methods. The study included a sample of 34 children - patients with cerebral palsy who had been treated in the Special Hospital for the Cerebral Palsy and Developmental Neurology in Belgrade. The patients were divided according to the determined diagnosis into two groups: Quadriparesis spastica (n = 11) and Morbus Little (n = 16). The children, aged 8-12 years, had preserved intelectual abilities, and all of them had preserved hearing. The study was conducted during the period from January to September 2009. The functional state of articulatory organs in both groups was tested by the C-test that examines the anatomic structure and mobility of the articulatory organs. Results. Our research showed that both groups of the patients had impaired functional state of the tongue - the most mobile articulatory organ. Also, the research showed that the functional state of the tongue was worse in children diagnosed with Quadriparesis spastica. A statistically significant correlation between the diagnosis and the functional state of the tongue, the tongue test performance and the retention of the tongue in a given position was found (r = 0.594, p < 0.005; r = 0.816, p < 0.01 and r = 0.738, p < 0.001, respectively). Conclusion. A large percentage of children with cerebral palsy were not able to establish control over the position of articulatory organs, especially the tongue, and its retention in a given position, all of which affect the quality of speech.